Primary Care Clinics and Accountable Care Organizations - Judith Ortiz PhD; Chiung-Ya Tang PhD; Yi-Ling Lin MS; Maysoun D. Masri ScD, MBA, MPH (SAGE Publishing, 2015)
Background: The Accountable Care Organization (ACO) is one of the new models of health care delivery in the United States. To date, little is known about the characteristics of health care organizations that have joined ACOs. We report on the findings of a survey of primary care clinics, the objective of which was to investigate the opinions of clinic management about participation in ACOs and the characteristics of clinic organizational structure that may contribute to joining ACOs or be willing to do so. Methods: A 27-item survey questionnaire was developed and distributed by mail in 3 annual waves to all Rural Health Clinics (RHCs) in 9 states. Two dependent variables-participation in ACOs and willingness to join ACOs-were created and analyzed using a generalized estimating equation approach. Results: A total of 257 RHCs responded to the survey. A small percentage (5.2%) of the respondent clinics reported that they were participating in ACOs. Rural Health Clinics in isolated areas were 78% less likely to be in ACOs (odds ratio = 0.22, P = .059). Nonprofit RHCs indicated a higher willingness to join an ACO than for-profit RHCs (B = 1.271, P = .054). There is a positive relationship between RHC size and willingness to join an ACO (B = 0.402, P = .010). Conclusion: At this early stage of ACO development, many RHC personnel are unfamiliar with the ACO model. Rural providers' limited technological and human resources, and the lack of ACO development in rural areas, may delay or prevent their participation in ACOs.